A multi-year record of atmospheric mercury species at a background mountain station in Andean Patagonia (Argentina): Temporal trends and meteorological influence. (1st October 2019) - Diéguez, María C.; Bencardino, Mariantonia; García, Patricia E.; D'Amore, Francesco; Castagna, Jessica; De Simone, Francesco; Soto Cárdenas, Carolina; Ribeiro Guevara, Sergio; Pirrone, Nicola; Sprovieri, Francesca
Abstract: This work provides the first continuous measurements of atmospheric mercury (Hg) at the EMMA Station in Patagonia (Argentina), within the Southern Volcanic Zone of South America. This monitoring site was set up by the Global Mercury Observation System (GMOS project) and is located inside Nahuel Huapi National Park (41°07′43.33″S, 71°25′12.03″W; 800 m a.s.l) in a forested valley of the Andes upwind of San Carlos de Bariloche city. This study aimed at describing atmospheric Hg levels and trends of variation using concentration data of Gaseous Elemental Mercury (GEM) collected from October 2012 to July 2017 and, Gaseous Oxidized Mercury (GOM) and Particle-Bound Mercury (PBM) recorded from March 2014 until July 2017. During the studied period the mean GEM concentration was 0.86 ± 0.16 ng m −3 ; with the highest level in the austral spring (0.95 ± 0.13 ng m −3 ) and the lowest in the autumn (0.80 ± 0.15 ng m −3 ). Mean GOM concentration was 4.61 ± 4.00 pg m −3, displaying the highest level in autumn (5.47 ± 4.39 pg m −3 ) and the lowest in winter (1.24 ± 0.90 pg m −3 ). Mean PBM computed for the whole period was 3.74 ± 3.41 pg m −3 ; with the highest mean levels recorded in autumn (6.32 ± 3.41 pg m −3 ) and the lowest in spring (1.18 ± 0.92 pg m −3 ). Daytime levels of GEM, GOM and PBM were higher than nighttime concentrations, although in the case GOM and PBM similar levels were computed in autumn and summer, respectively. Westerly winds along with temperature and relative humidity influenced the dynamics of GEM, GOM and PBM at the EMMA Station. The HYSPLIT model showed that the area of the EMMA station was simultaneously affected by local and regional sources (forest fires and volcanoes) while the lowest values were recorded with the inflow of clean oceanic air masses coming from the free troposphere and corresponding to a long-range transport. Moreover, the Potential Source Contribution Function analysis showed that emissions in the Marine Boundary Layer, deriving from remote areas of Pacific Ocean, are sources of GEM and GOM. Graphical abstract: Image 1 Highlights: Atmospheric mercury speciation (GEM, GOM, PBM) was measured in a Patagonian mountain station. GEM varied seasonally (spring > summer > winter and autumn) and daily (day > night). Pacific winds, temperature and humidity influenced GEM, GOM and PBM. Long- and short-range atmospheric transport influence GEM, GOM and PBM. Volcanoes and forest fires are regional/local mercury sources.